1984
DOI: 10.1126/science.6334363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Dopamine and Serotonin Receptors Measured by Positron Tomography in the Living Human Brain

Abstract: D2 dopamine and S2 serotonin receptors were imaged and measured in healthy human subjects by positron emission tomography after intravenous injection of 11C-labeled 3-N-methylspiperone. Levels of receptor in the caudate nucleus, putamen, and frontal cerebral cortex declined over the age span studied (19 to 73 years). The decline in D2 receptor in males was different from that in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(87 citation statements)
references
References 63 publications
5
80
2
Order By: Relevance
“…Secondly, data obtained using autoradiographic techniques, unlike PET, necessitate the use of postmortem material and thus are inherently subject to alterations due to tissue autolysis resulting perhaps, in an underestimation in receptor number (Brady and Mufson, 1990). The magnitude of the decrease in muscarinic cholinergic receptor binding observed in this study is consistent with that observed in the dopaminergic D, receptor system in male subjects using L"C1-3-N-methylspiperone and PET (Wong, et al, 1984). As only male volunteers were used in this study, we are unable to establish whether or not there are sex differences in [N-C-methyl]-benztropine binding similar to those reported by Wong and his colleagues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Secondly, data obtained using autoradiographic techniques, unlike PET, necessitate the use of postmortem material and thus are inherently subject to alterations due to tissue autolysis resulting perhaps, in an underestimation in receptor number (Brady and Mufson, 1990). The magnitude of the decrease in muscarinic cholinergic receptor binding observed in this study is consistent with that observed in the dopaminergic D, receptor system in male subjects using L"C1-3-N-methylspiperone and PET (Wong, et al, 1984). As only male volunteers were used in this study, we are unable to establish whether or not there are sex differences in [N-C-methyl]-benztropine binding similar to those reported by Wong and his colleagues.…”
Section: Discussionsupporting
confidence: 87%
“…With the development of selective radiolabelled tracers for different neurotransmitter systems, advances have been made in understanding both the underlying pathophysiology of some neurotransmitter-specific central nervous system (CNS) diseases (Wong, et al, 1986;Frost, et al, 1988;Lucignani, et al, 1990) as well as interactions occurring between one neurotransmitter system (muscarinic cholinergic) and another (dopaminergic) (Dewey, et al, 1988;1990a,b). PET studies designed to examine the effects of aging on the dopaniinergic D, and serotonergic receptor system have also been reported (Wong, et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…Under such conditions, the binding potential in target regions cannot be determined as a k3/k4 ratio from a compartment model, since k4 is extremely small and not significantly different from zero. It can be shown that for time intervals T >> 1/k2 and if k3 << k2, the target/nontarget ratio (B/F) of an irreversible antagonist will increase in the following way [29,30]:…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the human life span (18 to 73 years) the density of D2-like neuroreceptors in the caudate nucleus, the putamen, and the frontal cerebral cortex is inversely proportional to the age of the person [31] .…”
Section: D2-like Neuroreceptor Imaging Throughout the Lifespanmentioning
confidence: 99%
“…Serotonin 5-HT 2A receptors [ 11 C]NMSP was utilized to estimate the density and the distribution of cortical serotonin 5-HT 2A and striatal dopamine D2-like neuroreceptors in people with schizophrenia [31] . Reductions in the density of prefrontal cortical 5-HT 2A receptors have been demonstrated in some drug-naïve people with schizophrenia to confirm autopsy studies [11] .…”
Section: Imaging Serotonin Receptors In the Brain Of People With Schimentioning
confidence: 99%